Functional replacement of oxygen by other oxidants in articular cartilage. - Lee, R; Urban, J (2002)
OBJECTIVE: Articular cartilage chondrocytes consume remarkably little O(2) in comparison with most other animal cells; glycolysis forms the principal source of ATP in this cartilage. Although not lethal for many days, imposition of anoxia immediately lowers intracellular ATP, inhibits rates of glycolysis, and prevents articular chondrocytes from producing extracellular matrix macromolecules. This study was undertaken to investigate the role of O(2) in articular chondrocyte metabolism. METHODS: We examined the effects of oxygen and of several other classes of exogenous oxidants, i.e., 1) the dyes methylene blue and 2,6-dichlorophenol-indophenol, 2) the iron (III) complex ferricyanide, and 3) the keto-acids oxaloacetate and pyruvate (and phosphoenolpyruvate, a metabolic precursor of pyruvate), on rates of glycolysis and of sulfate incorporation by bovine articular cartilage in vitro. RESULTS: Lactate production was lowest under conditions of anoxia and was stimulated severalfold by addition of O(2) (air-saturated medium). Under strict anoxia, other oxidants restored lactate production to rates at least comparable with those seen in aerobic controls; under aerobic conditions, they had little effect. Oxygen and all of the other oxidants examined stimulated sulfate incorporation more strongly than lactate production. The compounds that promoted glycolysis and hence sulfate incorporation in cartilage under anoxia were themselves reduced; that is, they functioned as oxidants in lieu of O(2). CONCLUSION: For normal function, articular cartilage appears to require exogenous oxidants to stimulate glycolysis and produce ATP and extracellular matrix. Under physiologic conditions, oxygen acts as this oxidant, but its role can be adequately assumed by other agents.